If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1) + -1(4 + 2x) = 5 + x Reorder the terms: 2(-1 + 3x) + -1(4 + 2x) = 5 + x (-1 * 2 + 3x * 2) + -1(4 + 2x) = 5 + x (-2 + 6x) + -1(4 + 2x) = 5 + x -2 + 6x + (4 * -1 + 2x * -1) = 5 + x -2 + 6x + (-4 + -2x) = 5 + x Reorder the terms: -2 + -4 + 6x + -2x = 5 + x Combine like terms: -2 + -4 = -6 -6 + 6x + -2x = 5 + x Combine like terms: 6x + -2x = 4x -6 + 4x = 5 + x Solving -6 + 4x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6 + 4x + -1x = 5 + x + -1x Combine like terms: 4x + -1x = 3x -6 + 3x = 5 + x + -1x Combine like terms: x + -1x = 0 -6 + 3x = 5 + 0 -6 + 3x = 5 Add '6' to each side of the equation. -6 + 6 + 3x = 5 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = 5 + 6 3x = 5 + 6 Combine like terms: 5 + 6 = 11 3x = 11 Divide each side by '3'. x = 3.666666667 Simplifying x = 3.666666667
| 5x+8=8x-17 | | x^3-60x^2+1200x-8000=0 | | 4x+35=11x+4 | | 2+2=22 | | 2+(3-b)*3-11b= | | -5(2x-1)=-5 | | 10x-26=56+4 | | 3x+22=6x-5 | | 9x-30=61 | | -8x+8=-5x+2 | | 5x+-11=3x+-1 | | X-11/6=-4 | | 2/4-x^2-1/2x-4-7/2x^2+4x=0 | | 2/4-x^2-1/2x-4-72x^2+4x=0 | | 2x+6/6=1x+x/2 | | -9/-3 | | (6/5)3x5.2 | | 6/2(r+2)=16/2 | | 18+8x=27+5x | | x+(-2)=-1 | | 3(x+5)=10x+8 | | 2x-6x+40+6x=0 | | 3q-4=14 | | x-14=3x+4 | | 50+3y=7y | | 2x+12y-6=0 | | 611x+8=9x+19 | | x+[x*.05]=5.25 | | 5^3x=1/625 | | p=m-a/x-b | | p=m-a/x-b | | p=m-a/x-b |